Cryptosporidium parvum, Cryptosporidium ryanae, and Cryptosporidium bovis in samples from calves in Austria - Lichtmannsperger, Katharina (Parasitol Res, 2020)
Fecal samples of 177 calves of up to 180 days of age with diarrhea from 70 farms in Austria were examined to obtain information on the occurrence of Cryptosporidium species. Initially, all samples were examined by phase-contrast microscopy. Cryptosporidium-positive samples (55.4%; n = 98) were screened by gp60 PCR, resulting in 68.4% (n = 67) C. parvum–positive samples. The remaining 31 gp60-PCR-negative and the phase-contrast microscopy negative samples (n = 79) were screened by PCR targeting a 700 bp fragment of the 18S rRNA gene. Sequencing of the PCR products revealed the presence of C. parvum (n = 69), C. ryanae (n = 11), and C. bovis (n = 7). The latter two species have never been described in Austria. C. parvum–positive samples were genotyped at the gp60 gene locus, featuring four subtypes (IIaA15G2R1, IIaA21G2R1, IIaA19G2R1, IIaA14G1R1). The most frequently detected subtype IIaA15G2R1 (n = 52) was present in calves from 30 different farms. IIaA14G1R1 (n = 5) occurred on a single farm, subtype IIaA21G2R1 (n = 4) on two farms, and subtype IIaA19G2R1 (n = 4) on three farms. The results confirm the widespread occurrence of zoonotic C. parvum in diarrheic calves.